Death due to recurrent thromboembolism among younger healthier individuals hospitalized for idiopathic pulmonary embolism - White, Richard H.; Zhou, Hong; Murin, Susan (Thrombosis and Haemostasis, 2008)
The incidence of death due to recurrent pulmonary embolism (PE) after a first-time idiopathic PE is not well defined. We conducted a retrospective study of patients age 18 to 56 years who had idiopathic PE between 1994–2001.The incidence and cause of death within five years was determined using linked discharge records and a master death registry. A total of 3,456 patients had a first-time idiopathic PE. The rate of recurrent VTE 0–6 months after the index event was 13.1%/year, and 2.9%/year 6–60 months after the event. During the mean follow-up of 3.2 years 118 (3.4%, 95% confidence interval [CI]=2.8–4.1%) patients died. Fifty-two (44%) deaths occurred <29 days after the index PE (case-fatality rate =1.5%,95%CI=1.1–2.0%). Among the 66 cases (1.9%) that died after 28 days, 18 (0.52%) were due to recurrent PE or its sequelae: eight had recurrent PE alone, five had recurrent PE and a serious co-morbid illness, and five had thromboembolic pulmonary hypertension with or without acute PE. The person-time rate of death (deaths per 100 patientyears) attributed to any recurrent thromboembolism 6–60 months after the event was 0.16% (95%CI=0.1–0.26%). Ten of the 18 (56%) late thromboembolic deaths reflected a first-time recurrent PE. The 28-day case-fatality rate for recurrentVTE was 2.8% (95%CI= 1.5–4.9%).In this cohort of younger patients with idiopathic PE, the rate of death due to recurrentVTE, particularly to first-time recurrent PE, was low. Among the patients who died of thromboembolism >28 days after the index PE, 28% had developed pulmonary hypertension.
Keywords: Thromboembolism; epidemiology; PE; venous thrombosis; administrative data